2019
DOI: 10.1016/j.jalz.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amyloid β 40/42 ratio predicts cerebral amyloidosis in cognitively normal individuals at risk for Alzheimer's disease

Abstract: INTRODUCTION: Blood-based biomarkers of pathophysiological brain amyloid β (Aβ) accumulation, particularly for preclinical target and large-scale interventions, are warranted to effectively enrich Alzheimer's disease clinical trials and management. METHODS: We investigated whether plasma concentrations of the Aβ1-40/Aβ1-42 ratio, assessed using the single-molecule array (Simoa) immunoassay, may predict brain Aβ positron emission tomography status in a large-scale longitudinal monocentric cohort (N = 276) of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
100
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 148 publications
(122 citation statements)
references
References 46 publications
15
100
1
Order By: Relevance
“…We acknowledge that cross‐validation in external cohorts is essential. Of note, our results do not stand alone; multiple recent studies using highly sensitive immunoassays for blood‐based amyloid beta quantification showed capability to discriminate between amyloid‐positive and amyloid‐negative cognitively normal individuals, with or without subjective cognitive complaints, providing independent support for our findings. Moreover, in our article we not only investigated the association of plasma amyloid and CSF amyloid, but showed that low plasma amyloid levels are related to a higher risk of subsequent clinical disease progression to mild cognitive impairment or dementia.…”
supporting
confidence: 71%
“…We acknowledge that cross‐validation in external cohorts is essential. Of note, our results do not stand alone; multiple recent studies using highly sensitive immunoassays for blood‐based amyloid beta quantification showed capability to discriminate between amyloid‐positive and amyloid‐negative cognitively normal individuals, with or without subjective cognitive complaints, providing independent support for our findings. Moreover, in our article we not only investigated the association of plasma amyloid and CSF amyloid, but showed that low plasma amyloid levels are related to a higher risk of subsequent clinical disease progression to mild cognitive impairment or dementia.…”
supporting
confidence: 71%
“…The assessment of Ab by PET or CSF immunoassays is now included in research criteria for AD [46] as well as in the biological definition of the disease [47]. Ab peptides can be readily measured in plasma utilising ultra-sensitive immunoassays [5,6] or targeted mass spectrometry (MS) [3] and emerging evidence suggests that a decreased Ab peptide ratio can identify cerebral Ab-positive individuals with high sensitivity and specificity ( Table 2).…”
Section: Amyloid-bmentioning
confidence: 99%
“…One of the many challenges that the dementia community face is the detection of the pre-symptomatic phase of the AD using non-invasive, widely accessible and disease relevant biomarkers. In recent times, blood biomarkers have taken centre stage, with measurements of Ab species [3][4][5][6], the axonal injury marker neurofilament light (NfL) [7,8] and phosphorylated tau on threonine 181 (P-tau181) [9] showing much promise. There are now international efforts underway to progress these biomarkers to be applicable for clinical use [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in proteomic assays have demonstrated the potential use of plasma Aβ to identify brain Aβ‐positive individuals with moderate‐to‐high accuracy [4–8]. The measurement of T‐tau in plasma has limited diagnostic value, albeit being slightly but significantly increased in patients with AD [9] but promising data are emerging on P‐tau [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in proteomic assays have demonstrated the potential use of plasma Ab to identify brain Abpositive individuals with moderate-to-high accuracy [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%